Lembar Kerja Berbasis Discovery-Learning untuk Pembelajaran Matematika Penyajian Data Statistik Kelas VII - Satiti, Wisnu Siwi; Umardiyah, Fitri (Universitas KH. A. Wahab Hasbullah, 2022)
Students’understanding of mathematical concepts is important to be aquired, due to the use of mathematical concepts is variety of context in everyday life. One of the mathematical material that is widely used in real life is concept of Statistics: presenting statistical data. However, based on the facts in the field and results of several previous studies, they show that many students have difficulty presenting statistical data. This is due to a lack of initial understanding. Therefore, in this study, teaching materials are developed to support learning. In this study, Discovery Learning-based worksheets are developed on the material of presenting statistical data for Junior High School students (SMP/MTs). This study is a development research by applying ADDIE model. Based on results of expert validation, which is consist of mathematics lecturers and teachers, an average rating of 87.5% was obtained and met